Discovery of Antibiofilm Activity of Elasnin against Marine Biofilms and Its Application in the Marine Antifouling Coatings - Lexin Long; Ruojun Wang; Ho Yin Chiang; Wei Ding; Yong-Xin Li; Feng Chen; Pei-Yuan Qian (Marine Drugs, 2021)
Biofilms are surface-attached multicellular communities that play critical roles in inducing biofouling and biocorrosion in the marine environment. Given the serious economic losses and problems caused by biofouling and biocorrosion, effective biofilm control strategies are highly sought after. In a screening program of antibiofilm compounds against marine biofilms, we discovered the potent biofilm inhibitory activity of elasnin. Elasnin effectively inhibited the biofilm formation of seven strains of bacteria isolated from marine biofilms. With high productivity, elasnin-based coatings were prepared in an easy and cost-effective way, which exhibited great performance in inhibiting the formation of multi-species biofilms and the attachment of large biofouling organisms in the marine environment. The 16S amplicon analysis and anti-larvae assay revealed that elasnin could prevent biofouling by the indirect impact of changed microbial composition of biofilms and direct inhibitory effect on larval settlement with low toxic effects. These findings indicated the potential application of elasnin in biofilm and biofouling control in the marine environment.